Application of phytosynthesized silver nanoparticles (SNPs) against Erwinia amylovora causing fire blight disease - Saeed Tarighi; Meysam Soltani Nejad (Heliyon)
The bacterium Erwinia amylovora is responsible for the destructive disease known as fire blight in pear trees. This highly detrimental condition poses a significant threat to the health and vitality of these trees. The existing strategies for managing fire blight disease involve the regular use of copper compounds and streptomycin, particularly during periods when environmental factors are conducive to the spread of the infection. Silver nanoparticles, also known as SNPs, are tiny specks of silver ranging in size from 10 to 100 nm. These particles are created through various chemical and biological processes. Numerous studies have demonstrated their ability to exhibit antibacterial properties against a wide range of human and animal pathogens. In this investigation, the dimensions of SNPs were ascertained by employing aqueous extracts derived from apple, pear, and quince leaves. The average sizes of the SNPs were found to be approximately 30 nm, 38 nm, and 55 nm, apple, quince and pear respectively. The pear mature fruits successfully managed to control the rot caused by the disease-causing E. amylovora. This study shows the viability of utilizing leaves extract from apple, pear, and quince as a suitable medium for the production of silver nanoparticles. These nanoparticles hold potential for effectively managing fire blight disease.